Seroprevalence of transfusion transmissible infections among blood donors at a tertiary care hospital in urban area of Nepal - Nepal, Bipin; Maharjan, Sabindra; Bhasima, Sunil; Adhikary, Achyuta; Ghimire, Akriti; Bhurtel, Prajwol; Vaidya, Krijan Man (Grande Medical Journal, 2024)
BackgroundInfection with hepatitis B virus (HBV), hepatitis C virus (HCV), human Immunodeficiency Virus (HIV) and syphilis are serious complications of blood transfusion. These infections are always screened by blood banks. Such tests are mandatory for transfusion safety in Nepal and the entire world. This study was aimed at determining the seroprevalence of HBV, HCV, syphilis and HIV.MethodA retrospective analysis of blood donor data from June 2017 to May 2020 was conducted at Blood Bank of Grande International Hospital, Kathmandu, Nepal. Sera samples were screened for hepatitis B surface antigen (HBsAg), antibodies to hepatitis C virus (HCV), human immunodeficiency virus (HIV) 1 & 2 by Enhanced Chemiluminance Assay method, using diagnostic kit from Johnson & Johnson at Vitros 5600 machine and by Immunochromatography method for Treponema pallidum antibody, commercially available immunochromatography based kits from SD biosensor.ResultOut of 8811 candidate blood donors, 133 (1.5%) donors were serologically reactive with either one of Transfusion Transmitted Infection. Seroprevalence of HIV, HBV, HCV and syphilis infection was 0.17%, 0.39%, 0.28% and 0.65% respectively. The prevalence of TTIs was 1.55% for male and 1.31 % for female in the donation population.ConclusionThe prevalence of HIV, HBV, and HCV was higher in male donor whereas syphilis show high prevalence among the female donors. According to age group HIV prevalence was highest among blood donors of the age group 21 to 30 years of age.